A review of the perceived barriers within the Health Belief Model on Pap smear screening as a cervical cancer prevention measure - Julinawati, Suanda; Cawley, Desmond; Domegan, Christine, Dr.; Brenner, Maria, Dr.; Rowan, Neil J (Asian Economic and Social Society, 2013)
Link to publisher's homepage at http://www.aessweb.com/